Role of Gene Polymorphisms in the Development of Aseptic Loosening of Knee and Hip Prostheses: A Review - Alexandr D. Kamenskiy; Alexandra I. Don'kina; Yuri V. Parakhin; Olga G. Kovtun; Mikhail V. Parshikov (Travmatologiâ i Ortopediâ Rossii)
Background. Aseptic loosening is a significant issue in the endoprosthetics of major joints of the lower limbs. In the modern view, aseptic loosening of joint prostheses is primarily caused by prolonged inflammation, which induces periprosthetic osteolysis. Various factors, such as sex, age, activity level, and others, can influence the development of periprosthetic osteolysis and aseptic loosening. Some researchers attribute to the factors gene polymorphisms related to inflammation, bone metabolism, and other processes. Understanding the connection between specific genetic markers and the development of endoprosthetic complications can provide deeper insights into the mechanisms of periprosthetic osteolysis and aseptic loosening, as well as allow for better prediction of complications in patients.